2021
DOI: 10.1038/s41598-021-99164-5
|View full text |Cite
|
Sign up to set email alerts
|

Using machine learning methods for supporting GR2M model in runoff estimation in an ungauged basin

Abstract: Estimating monthly runoff variation, especially in ungauged basins, is inevitable for water resource planning and management. The present study aimed to evaluate the regionalization methods for determining regional parameters of the rainfall-runoff model (i.e., GR2M model). Two regionalization methods (i.e., regression-based methods and distance-based methods) were investigated in this study. Three regression-based methods were selected including Multiple Linear Regression (MLR), Random Forest (RF), and M5 Mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…While the current study focused on the RR modeling concept by considering all inputs at the t (same) time and by conserving several meteorological variables as input of black-box models to have interpretation meaning for RR modeling. Previous researches confirm the result of the current study, for example, Ditthakit et al 13 used the black-box model to increase the efficiency of the white-box model in Thailand. This means that the method presented in this study can be expanded by other models and also can generalize the implementation of this method in other regions with different climates.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…While the current study focused on the RR modeling concept by considering all inputs at the t (same) time and by conserving several meteorological variables as input of black-box models to have interpretation meaning for RR modeling. Previous researches confirm the result of the current study, for example, Ditthakit et al 13 used the black-box model to increase the efficiency of the white-box model in Thailand. This means that the method presented in this study can be expanded by other models and also can generalize the implementation of this method in other regions with different climates.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, various meteorological and climatological variables like temperature, evaporation, humidity, and air pressure provoke the volume of runoff 9 . The nature of hydrological systems could be monitored through the various types of hydrological models which give a deeper insight into the physical interaction between the various parameters and their response to each other 10 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The GR2M is a conceptual monthly hydrological model developed by Makhlouf in 1990s [37] which has been continuously updated by many researchers and employed in many areas across the world [38][39][40][41][42][43][44]. The structures and equations of the GR2M model are shown in Figure 2.…”
Section: Hydrological Modelmentioning
confidence: 99%
“…Multiple time-series issues require prediction of a sequence of future values using only observed historical data [10][11][12][13][14][15]. Multistep-ahead prediction describes the process of attempting to forecast potential events in a time series [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have applied SVR, RF, and ANN in the literature. For example, Yang et al [12] found a difference in the performance of SVR, RF, and the artificial neural network (ANN) for predicting one-month-ahead reservoir water inflows in China and the USA. The results show the RF technique has the highest performance with important climate indices such as NINO1, NINO3, NINO4, etc.…”
Section: Introductionmentioning
confidence: 99%